2003
DOI: 10.1046/j.1439-0450.2003.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection by Cryptosporidium  parvum and Porcine Circovirus Type 2 in Weaned Pigs

Abstract: Routine histopathological diagnosis of one representative 3-month-old pig from a group suffering from diarrhoea revealed a massive degree of parasitation by Cryptosporidium parvum, with a concomitant infection by porcine circovirus type 2 (PCV2), that was confirmed by immunohistochemical procedures. The areas of intestine where parasites were more numerous presented abundant PCV2 infected cells in mucosa and submucosa. The concurrence of C. parvum, a rare primary intestinal pathogen in post-weaning and growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…While co-infection of BRV-A and C. parvum in diarrheic calves has been frequently reported (Bartels et al, 2010;Bjorkman et al, 2003;de la Fuente et al, 1999;Garcia et al, 2000;Uhde et al, 2008), common association of Nebovirus and C. parvum in diarrheic animals is a new observation. It has been reported that viral infections, such as porcine circovirus type 2 and human immunodeficiency virus, can increase the susceptibility of pigs and humans, respectively, to C. parvum (Nunez et al, 2003;Putignani and Menichella, 2010), suggesting that immunosuppressive viruses can predispose animals or humans to C. parvum. In the absence of effective treatment options for C. parvum, it may be prudent to rely on management practices and specific aids in prevention of viral infections to reduce clinical problems with C. parvum infections.…”
Section: Discussionmentioning
confidence: 99%
“…While co-infection of BRV-A and C. parvum in diarrheic calves has been frequently reported (Bartels et al, 2010;Bjorkman et al, 2003;de la Fuente et al, 1999;Garcia et al, 2000;Uhde et al, 2008), common association of Nebovirus and C. parvum in diarrheic animals is a new observation. It has been reported that viral infections, such as porcine circovirus type 2 and human immunodeficiency virus, can increase the susceptibility of pigs and humans, respectively, to C. parvum (Nunez et al, 2003;Putignani and Menichella, 2010), suggesting that immunosuppressive viruses can predispose animals or humans to C. parvum. In the absence of effective treatment options for C. parvum, it may be prudent to rely on management practices and specific aids in prevention of viral infections to reduce clinical problems with C. parvum infections.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidium oocysts have been detected in the faeces or slurry of pigs in Australia (Johnson et al, 2008; McCarthy et al, 2008; Ryan et al, 2003), Brazil (Fiuza et al, 2011), Canada (Budu-Amoako et al, 2012; Farzan et al, 2011; Guselle et al, 2003; Olson et al, 1997; Sanford, 1987), China (Chen et al, 2011; Wang et al, 2010; Yin et al, 2011), Croatia (Bilic and Bilkei, 2006), Czech Republic (Jeníková et al, 2011; Kváč et al, 2009a,c; Vítovec et al, 2006), Denmark (Langkjær et al, 2007; Maddox-Hyttel et al, 2006), England (Featherstone et al, 2010), Germany (Epe et al, 2004; Wieler et al, 2001), Ireland (Zintl et al, 2007), Italy (Canestri Trotti et al, 1984), Japan (Izumiyama et al, 2001), Korea (Rhee et al, 1991), Nigeria (Yatswako et al, 2007), Norway (Hamnes et al, 2007), Spain (Nunez et al, 2003; Quilez et al, 1996; Reinoso and Becares, 2008; Villacorta et al, 1991), Switzerland (Ebeid et al, 2003), Taiwan (Hsu et al, 2008), Trinidad and Tobago (Adesiyun et al, 2001), and USA (Atwill et al, 1997; Bergeland, 1977; Kennedy et al, 1977; Tacal et al, 1987; Xiao et al, 1994; Xiao et al, 2006). Cryptosporidium pig genotype II was reported in domestic pigs in nine countries.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Madec et al (2000), o período de transmissão ocorreria entre a 5ª e a 16ª semanas, com fase crítica e mortes ocorrendo por volta da 13ª semana. Com freqüência observa-se co-infecção por Mycoplasma hyopneumoniae (Pneumonia enzoótica), Escherichia coli (Colibacilose), Actinobacillus pleuropneumoniae (antiga Pleuropneumonia por Haemophilus), Haemophilus parasuis (Doença de Glässer), Salmonella sp, Staphylococcus sp, PRRSV (Sorden 2000) e, menos freqüentemente, com Pneumocystis carinii (Clark 1997) e Cryptosporidium parvum (Nunez et al 2003).…”
Section: Resul II Resul Ii Resul Ii Resul Ii Results T T T Tadunclassified